RATTAN DIVERSITY AND BROAD EDAPHIC NICHES IN A TROPICAL RAINFOREST OF BUTON, SULAWESI, INDONESIA - ROSIE PRITCHETT; AURORA PHILLIPS; ANI MARDIASTUTI; ANDREW POWLING (BRIN Publishing (Penerbit BRIN), 2016)
PRITCHETT, R., PHILLIPS, A., MARDIASTUTI, A. & POWLING, A. 2016. Rattan diversity and broad edaphic niches in a tropical rainforest of Buton, Sulawesi, Indonesia. Reinwardtia 15(2): 99 – 110. — This paper attempts to answer the question: how can at least 20 species of rattan palms in the genus Calamus (family Palmae (Arecaceae)) co -exist in a rainforest? A survey of rattans was made in Lambusango Forest on Buton, an island close to south east Sulawesi, in Indonesia. Rattan species and numbers were recorded in 87 quadrats of 30 × 10 m, laid out along linear transects in habitats with a variety of soils. Evidence for edaphic (soil) niches was sought. Different rattan species were found to be adapted to soils with different conductivity and pH values. Standardised mean difference (d) scores were calculated for pairs of species based on their response to soil pH. Of the 66 pairs tested, 61 were found to be significantly different statistically. Such differences suggest, but do not prove, that many species occupy different edaphic niches. It was found that species which show a preference for soils with intermediate pH values (5.0 to 6.5) can grow in soils with a wide range of pH values, implying broad edaphic niches and that competition between these species is weak. Correspondence analysis shows that many species do not distinguish greatly between many soils with intermediate pH values. It is concluded that rattan species show evidence for having different edaphic niches, although the niches for many species are broad. It is speculated that many rattan species may be ecologically equivalent and that a weak version of ecological neutrality theory may apply.